Chile and the inter-war world: dynamics of the American international system in the context of the Chaco War and the role of international actors (Neutrals Commission, ABCP, League of Nations). (Revista de Estudios Europeos, 2024)
The inter-war period (1919-1939) was characterised by important changes in the dynamics of the functioning of the international system due to the emergence of new actors and supranational organisations that took on active roles in the search for solutions to the conflicts that developed during this period. Within the American international system, one of the most relevant conflicts was the Chaco War (1932-1935), which pitted Bolivia against Paraguay. The aim of this article is to characterise the American international system by studying the dynamics adopted by the different international actors in the face of war and the search for peace. We argue that the foreign policy of the American states involved in the search for peace in the Chaco War (mainly Chile, Argentina and the United States) was strongly conditioned by their respective national and hemispheric objectives, regional rivalries and mistrust of the role of the League of Nations.
Keywords: Chile; Interwar; Diplomacy; Chaco War; League of Nations